2016
DOI: 10.1007/s40503-016-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental and social attitudes, and family concerns on willingness to pay for improved air quality: a contingent valuation application in Mexico City

Abstract: By means of a single-bounded, referendum format contingent valuation, this paper estimates willingness to pay (WTP) for improved air quality among residents of Mexico City Metropolitan Area (MCMA). Findings from this paper illustrate heterogeneity in WTP associated with environmental and social attitudes, and family concerns. For instance, WTP is higher than average if respondents state a very high priority to air pollution but smaller than average if respondent's household contains more adults than the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
(40 reference statements)
2
11
0
Order By: Relevance
“…This is rife in numerous international based studies. In the Latin American context, a number of studies have examined the relationship between air quality and property value (Filippini and Martínez-Cruz, 2016). In Columbia, and primarily the J o u r n a l o f E u r o p e a n R e a l E s t a t e R e s e a r c h Bogotá region, Carriazo, Ready, and Shortle (2013) developed a hedonic price approach to estimate the value for an improvement in air quality based on rental property values.…”
Section: Literaturementioning
confidence: 99%
“…This is rife in numerous international based studies. In the Latin American context, a number of studies have examined the relationship between air quality and property value (Filippini and Martínez-Cruz, 2016). In Columbia, and primarily the J o u r n a l o f E u r o p e a n R e a l E s t a t e R e s e a r c h Bogotá region, Carriazo, Ready, and Shortle (2013) developed a hedonic price approach to estimate the value for an improvement in air quality based on rental property values.…”
Section: Literaturementioning
confidence: 99%
“…Among these, CBA is probably the most frequently used tool requiring environmental valuation [25]. For example, cost-benefit analysis based on contingent valuation for improved air quality conducted for Mexico City indicated that benefits from improved air quality surpass the costs of investing in hybrid buses [26].…”
Section: Ligus Mmentioning
confidence: 99%
“…Filippini et al [19] show that older respondents tend to report higher willingness to pay for improved air pollution. Buehn et al [20] further indicate that the elderlys' demand for environmental quality is higher than younger residents.…”
Section: Smog Consciousnessmentioning
confidence: 99%